1998
DOI: 10.1097/00001756-199806010-00022
|View full text |Cite
|
Sign up to set email alerts
|

Medullary swallowing-related neurons in the anesthetized cat

Abstract: Swallowing-related neurons (SRNs) were recorded systematically in the medulla oblongata of urethane-anesthetized cats. The SRNs received orthodromic inputs from the superior laryngeal nerve (SLN) and showed transient changes in their activity synchronous with swallowing. These neurons could be divided into three types. Type I SRNs are sensory-relay neurons from the SLN in the nucleus of the tractus solitarius (NTS), type II are interneurons located diffusely in the parvocellular reticular formation ventral to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 13 publications
5
61
1
Order By: Relevance
“…These findings indicate that, although some portion of respiratory neurons might contribute to the swallow-related laryngeal movements, the role of most respiratory neurons in swallowing is minor. It is suggested that the additional swallowing-network neurons are recruited to produce the swallow-related movements of the larynx (Umezaki et al, 1998b;Jean, 2001). Our data cannot exclude the possibility that extra premotor neurons other than the members of the respiratory network are recruited to inhibit ELMs during the expulsive phase of coughing and sneezing.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…These findings indicate that, although some portion of respiratory neurons might contribute to the swallow-related laryngeal movements, the role of most respiratory neurons in swallowing is minor. It is suggested that the additional swallowing-network neurons are recruited to produce the swallow-related movements of the larynx (Umezaki et al, 1998b;Jean, 2001). Our data cannot exclude the possibility that extra premotor neurons other than the members of the respiratory network are recruited to inhibit ELMs during the expulsive phase of coughing and sneezing.…”
Section: Discussionmentioning
confidence: 71%
“…Poliaček et al (2005) argued that neurons of the medullary lateral tegmental field, the raphe nuclei, and the pontine respiratory group are essential for the configuration of the central cough motor pattern of the larynx on the basis of the experimental results of kainic acid injection into the brainstem. Furthermore, some investigators have argued that nonrespiratory neurons in the reticular formation between the nucleus ambiguus and the nucleus of the solitary tract are also involved in the CPGs of coughing (Gestreau et al, 1997), sneezing (Wallois et al, 1997), and swallowing (Umezaki et al, 1998b(Umezaki et al, , 2005Jean, 2001). It is thus suspected that the laryngeal movements during nonrespiratory behaviors such as coughing, sneezing, and swallowing are generated not only by premotor neurons in the respiratory neuronal network, but also by nonrespiratory premotor neurons.…”
Section: Discussionmentioning
confidence: 99%
“…These provide sensory information from the oropharyngeal receptors to the higher nervous centers and are not part of the swallowing CPG network (27). Microelectrode recordings performed on sheep, rat, dog, cat, and monkey place the NTS in the dorsal swallowing group as part of the brainstem swallowing neurons (1,7,9,15,28,31,35,38,46,60). In humans, the cervical esophagus is composed of striated muscles that are innervated by the lower motor neurons.…”
Section: Discussionmentioning
confidence: 99%
“…During the esophageal phase of swallowing, activation of premotor neurons associated with the proximal esophagus inhibits premotor neurons associated with the distal esophagus [56]. This inhibitory response is followed by excitation [56,93]. Thus, the polarization of the inhibitory drive of premotor neurons from more proximal structures onto premotor neurons of more distal structures guarantees not only that the more proximal structures are connected to the more distal structures, but that this activation progresses only in one direction.…”
Section: Within-phase Coordinationmentioning
confidence: 99%
“…This coordination involves both excitatory and inhibitory mechanisms. In anesthetized sheep, activation of the pharyngoesophageal swallow by SLN stimulation activates pharyngeal premotor neurons simultaneous with inhibition of esophageal premotor neurons [56], and pharyngeal distension [93] inhibits esophageal premotor neurons. This inhibition is also manifested as hyperpolarization of esophageal motor neurons of the NA.…”
Section: Between-phase Coordinationmentioning
confidence: 99%